PENINGKATAN MINAT DAN HASIL BELAJAR SISWA DENGAN METODE PEMBELAJARAN QUIZ TEAM ”THINK FAST DO BEST” PADA MATERI REAKSI OKSIDASI-REDUKSI DI KELAS X MAN MODEL SINGKAWANG - Sutardi Sutardi; Rahmi Nuraztia; Sugianto Adi Saputra (Kaunia: Integration and Interconnection Islam and Science, 2013)
Learning has been done using the quiz team "think fast do best" for material Reaction of Oxidation Reduction in class X MAN Model Singkawang academic year 2011/2012. The main purpose of the creation method of quiz team "think fast do best" is to increase interest and student learning outcomes that previously could not be done with the lecture method. Learning quiz team method begins by dividing students into small groups. All members of the group together to learn the subject matter guided by the teacher, and then continued by discussing the worksheets to reinforce students' understanding. After finishing the discussion, held an academic competition in the form of a quiz. In practice, the quiz can be provided with a variety of simulation/games to reduce boredom in the classroom learning. Quiz team "think fast do best" methods was created as an alternative exciting quiz game that has many advantages, such as, can simultaneously determine students' progress, diagnose students' learning difficulties, enhance cooperation of students in learning, provide feedback, increased interest and motivation of students to learn better, and can instill character values in students. In addition, the results of observation and student questionnaire shown that the quiz team "think fast do best" method made to increase student interest and proven to help students to understand the subject matter, particularly the matter oxidation numbers, as demonstrated by the results of post-test and test formative (daily tests) where the majority of students get good value (above KKM set).